Review on Surface Elements and Bacterial Biofilms in Plant-Bacterial Associations - Niazi, Parwiz; Monib, Abdul Wahid; Ozturk, Hamidullah; Mansoor, Mujibullah; Azizi, Azizaqa; Hassand, Mohammad Hassan (Journal for Research in Applied Sciences and Biotechnology, 2023)
In recent years, there has been increasing interest in the function of bacterial surface elements and functional signals in biofilm formation. Plant-associated bacteria can significantly affect the health and productivity of a plant because they are found in many different areas of the plant, including roots, transport channels, stems, and leaves. The management of these compounds by plants is still unknown, although biofilm production on plants is associated with both symbiotic and pathogenic responses. While some of the bacteria found in biofilm matrices trigger pathogenesis, others can promote plant thriving and serve as biocontrol agents for phytopathogens. This detailed review discusses in depth the various elements and methods involved in the production of bacterial biofilms on plant surfaces and their attachment, as well as the relationship between these factors and bacterial activity and survival.